Bordetella bronchiseptica diguanylate cyclase BdcB inhibits the type three secretion system and impacts the immune response - Belhart, Keila (2023)
Bordetella bronchiseptica is a gram-negative bacterium that causes respiratory diseases in diferent animals, including mice, making B. bronchiseptica the gold-standard model to investigate host– pathogen interaction at the molecular level. B. bronchiseptica utilizes many diferent mechanisms to precisely regulate the expression of virulence factors. Cyclic di-GMP is a second messenger synthesized by diguanylate cyclases and degraded by phosphodiesterases that regulates the expression of multiple virulence factors including bioflm formation. As in other bacteria, we have previously shown that c-di-GMP regulates motility and bioflm formation in B. bronchiseptica. This work describes the diguanylate cyclase BdcB (Bordetella diguanylate cyclase B) as an active diguanylate cyclase that promotes bioflm formation and inhibits motility in B. bronchiseptica. The absence of BdcB increased macrophage cytotoxicity in vitro and induced a greater production of TNF-α, IL-6, and IL-10 by macrophages. Our study reveals that BdcB regulates the expression of components of T3SS, an important virulence factor of B. bronchiseptica. The Bb∆bdcB mutant presented increased expression of T3SS-mediated toxins such as bteA, responsible for cytotoxicity. Our in vivo results revealed that albeit the absence of bdcB did not afect the ability of B. bronchiseptica to infect and colonize the respiratory tract of mice, mice infected with Bb∆bdcB presented a signifcantly higher proinfammatory response than those infected with wild type B. bronchiseptica.